Nucleotide-Binding Oligomerization Domain-Containing Protein 2 Variants in Patients with Spontaneous Bacterial Peritonitis - Harputluoglu, Murat M. M.; Dertli, Ramazan; Otlu, Baris; Demirel, Ulvi; Yener, Ozkan; Bilgic, Yilmaz; Cagin, Yasir Furkan (Springer, 2016)
The occurrence of spontaneous bacterial peritonitis (SBP) is significantly increased in carriers of nucleotide-binding oligomerization domain-containing protein 2 (NOD2) variants, suggesting that local immune alterations might be implicated in bacterial translocation (BT). We aimed to assess the role of the NOD2 gene in conferring susceptibility to SBP. We also sought to determine whether levels of serum interleukin-6 (IL-6), lipopolysaccharide-binding protein, and soluble TNF-alpha receptor, along with the presence of bacterial DNA (bactDNA) in ascitic fluid, are appropriate markers for BT in patients with liver cirrhosis and SBP. A cohort of 171 patients was divided into two groups: patients with SBP (n = 82) and those without SBP (n = 89). The presence of the most common NOD2 variants (p.R702W, p.G908R, and c.3020insC) was determined in these patients. We detected the p.G908R variant in four patients (4.9 %) of the SBP group. No significant difference was observed between the SBP and non-SBP groups for NOD2 risk variants. The frequency of bactDNA in ascitic fluid was higher for patients with NOD2 variants than for patients without variants (p = 0.021). Serum IL-6 levels in the SBP group were higher than those in the non-SBP group. The frequent detection of bactDNA in ascites of patients with the p.G908R variant suggests there is a strong association between NOD2 risk variants and BT in SBP patients. In addition, increased serum IL-6 levels and bactDNA in ascitic fluid could be considered surrogate markers for BT in patients with cirrhosis.
Keywords: NOD2; Bacterial translocation; Spontaneous bacterial peritonitis; Cirrhosis